Das Wunder der Heliane opera in three acts, op. 20 (1857), after "Die Heilige" by Hans Kaltneker - Korngold, Erich Wolfgang 1897-1957 (Naxos, 2019)
"'Erich Wolfgang Korngold regarded Das Wunder der Heliane as his greatest work, but the opera has been neglected since its premiere in 1927. [...] Bonus materials include a rare audio recording of the Interlude to Act III recorded in 1928, as well as a picture gallery of rare images provided by Korngold specialist Brendan G. Carroll." [www.news.imz.at]
Bildformat 16:9
Keywords: Film; DVD-Video